Microplastic Pollution in The Marine Ecosystems: A Forensic Approach to Source Identification and Mitigation - Krishnan Ramesh; Jeyachandran, S. (International Journal of Accounting and Economics Studies, 2025)
Microplastics (MPs) pose growing ecological and economic risks in marine ecosystems, particularly due to their persistence, bioaccumulation, and impact on fisheries and tourism. This study presents a forensic investigation framework for identifying MP sources and proposes economically viable mitigation strategies. Emphasis is placed on cost-benefit analyses of MP control interventions such as pellet-capturing systems, periodic beach cleanup drives, and recycling incentives for fishing gear. The economic burden of inaction, ranging from seafood contamination to public health risks, is discussed about ecosystem service losses and coastal productivity declines. Using FTIR spectroscopy and morphological classification, the study systematically traces pollution patterns along India’s southern coastline. Further, the paper explores regulatory mechanisms and policy incentives, including extended producer responsibility (EPR), ESG-aligned investments, and polluter-pays frameworks, to promote compliance and governance transparency. The integration of environmental forensics with financial accountability tools strengthens the case for stakeholder-driven marine plastic governance. By incorporating economic reasoning and governance frameworks, this paper aligns microplastic mitigation with broader goals of sustainable blue economy development. The proposed framework supports both scientific inquiry and policy reform, offering scalable models for pollution management in emerging coastal economies.